Thermosensory thalamus: parallel processing across model organisms - Leva, Tobias M.; Whitmire, Clarissa J. (Frontiers in Neuroscience, 2023)
The thalamus acts as an interface between the periphery and the cortex, with nearly every sensory modality processing information in the thalamocortical circuit. Despite well-established thalamic nuclei for visual, auditory, and tactile modalities, the key thalamic nuclei responsible for innocuous thermosensation remains under debate. Thermosensory information is first transduced by thermoreceptors located in the skin and then processed in the spinal cord. Temperature information is then transmitted to the brain through multiple spinal projection pathways including the spinothalamic tract and the spinoparabrachial tract. While there are fundamental studies of thermal transduction via thermosensitive channels in primary sensory afferents, thermal representation in the spinal projection neurons, and encoding of temperature in the primary cortical targets, comparatively little is known about the intermediate stage of processing in the thalamus. Multiple thalamic nuclei have been implicated in thermal encoding, each with a corresponding cortical target, but without a consensus on the role of each pathway. Here, we review a combination of anatomy, physiology, and behavioral studies across multiple animal models to characterize the thalamic representation of temperature in two proposed thermosensory information streams.